PENGARUH GAYA KEPEMIMPINAN KOMANDO DAN KOMUNIKASI INTERPERSONAL TERHADAP TINGKAT KINERJA BAWAHAN DI SEKSI SIM DITLANTAS POLDA JATIM - Fuji Antoro Putro; Solikhah Yuliatiningtyas, P.Hd; Dr. Tony S. Soekrani, M.Si. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
This research was conducted on the basis of revealing the influence of the Command Leadership Style and Interpersonal Communication of leaders on the performance carried out by their subordinates. In addition, this study aims to obtain further clarity about the level of increase in the performance of subordinates of the SIM section of the East Java Regional Police which is the influence of the application of Leadership Style and Interpersonal Communication by their leaders. The research was conducted using a quantitative approach with a survey method through distributing and filling out questionnaires, the data collected will be processed and analyzed using testing with the help of the SPSS 26 for windows application. The results of the study showed that significantly and partially the Command Leadership Style and Interpersonal Communication on the Performance Level of subordinates. Through this research, it is hoped that it will be able to contribute to other papers and the agencies studied.